Exploring essential oils as prospective therapy against the ravaging Coronavirus (SARS-CoV-2) - Emmanuel Onah Ojah (Emergency Department of Hospital San Pedro (Logroño, Spain), 2020)
Introduction: Aromatic plants produce diverse chemical constituents with potential to inhibit viral infections. These plants have been utilized for the prevention and treatment of a range of infectious and non-infectious diseases. Essential oils are among the plant-derived antiviral agents that are being employed in phytomedicine, and are considered as prospective drug candidate against the ravaging Coronavirus. Methods: Relevant articles relating to the concept were identified using a combination of manual library search as well as journal publication on the subject and critically reviewed. Results: Essential oils in medicinal plants have extensive applications in medicinal chemistry, aromatherapy and pharmaceuticals. Essential oils have several biological properties such as antibacterial, antifungal, antiviral, antioxidant, anti-inflammatory, wound-healing and anti-cancer effects in vitro and in vivo. Several reports have analyzed and described essential oils as good antiviral agents against Respiratory tract viral infections hence are excellent prospective candidate against Corona virus. Conclusions: It is hoped that efficient and effective exploration and optimization of essential oils from medicinal plants would improve the drug discovery process against the ravaging Coronavirus.